2015
DOI: 10.1093/brain/awv165
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal activation of auditory regions during visuo-spatial working memory in early deafness

Abstract: Early deafness can reshape deprived auditory regions to enable the processing of signals from the remaining intact sensory modalities. Cross-modal activation has been observed in auditory regions during non-auditory tasks in early deaf subjects. In hearing subjects, visual working memory can evoke activation of the visual cortex, which further contributes to behavioural performance. In early deaf subjects, however, whether and how auditory regions participate in visual working memory remains unclear. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
91
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 106 publications
12
91
3
Order By: Relevance
“…This view is consistent with recent evidence that cross-modal visual recruitment of the pSTS was associated with increased functional connectivity with the calcarine cortex in the deaf although the directionality of the effect was undetermined (40). The hypothesis that the auditory cortex participates in early sensory/perceptual processing after early auditory deprivation, in contrast with previous assumptions that such recruitment manifests only for late and higher level cognitive process (41,42), also finds support in our MEG finding that a face-selective response occurs at about 196 ms in the right dTFA. The finding that at least 150 ms of information accumulation is necessary for highlevel individuation of faces in the cortex (22) suggests that the faceselective response in the right dTFA occurs immediately after the initial perceptual encoding of face identity.…”
Section: Discussionsupporting
confidence: 89%
“…This view is consistent with recent evidence that cross-modal visual recruitment of the pSTS was associated with increased functional connectivity with the calcarine cortex in the deaf although the directionality of the effect was undetermined (40). The hypothesis that the auditory cortex participates in early sensory/perceptual processing after early auditory deprivation, in contrast with previous assumptions that such recruitment manifests only for late and higher level cognitive process (41,42), also finds support in our MEG finding that a face-selective response occurs at about 196 ms in the right dTFA. The finding that at least 150 ms of information accumulation is necessary for highlevel individuation of faces in the cortex (22) suggests that the faceselective response in the right dTFA occurs immediately after the initial perceptual encoding of face identity.…”
Section: Discussionsupporting
confidence: 89%
“…The present study provided additional evidence supporting strengthened functional links between the visual stream and the salient core hubs, which may partly interpret the compensatory changes in non-visual perceptual181920232425 and cognitive performance in blind individuals262728. This inference was supported by a recent serial study by Ding et al ., who reported cross-modal activation of auditory regions during visuospatial working memory in early deafness42; moreover, strengthened functional connectivity has been shown between these reshaped auditory regions and the AI in early deafness, and the strengthened functional connectivity is significantly associated with the working memory performance43. Because the present study did not acquire the behaviour information, the direct association between the visual-AI functional coupling and the non-visual functions requires future clarification.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have indicated the plastic potential of the AI in response to sensory deprivation. For example, early deaf individuals demonstrate stronger activation of the AI during visual short-term verbal memory task4142, as well as a strengthened functional connectivity (FC) between the AI and the superior temporal sulcus, where cross-modal processing of the visual spatial working memory have been identified compared with hearing subjects43. Compared with the sighted subjects, the congenitally blind (CB) individuals demonstrate decreased regional homogeneities of the AI44.…”
mentioning
confidence: 99%
“…The fMRI, PET and SPECT are the most commonly used techniques to evaluate the changes [2224]. Blood oxygen level, regional cerebral blood flow or FDG uptakes are measured by these methods and can definitively reflect changes in the underlying neuronal activity.…”
Section: Discussionmentioning
confidence: 99%